Integrating Multiple Intelligences in Teaching Materials to Enhance Students’ Critical Thinking: A Literature Review - Suryani, Ai; Warastuti, Renaning; Permana, Irvan (Universitas Negeri Semarang, 2025)
Critical thinking skills are essential competencies that students must possess to face 21st-century challenges. However, studies indicated that students' critical thinking skills in Indonesia remain unsatisfactory and, thus, need suitable approaches. One of the approaches believed to cope with this issue is the Multiple Intelligences. This article aims to examine the contribution of the Multiple Intelligences approach to developing teaching materials that foster students' critical thinking abilities. This study utilized a Systematic Literature Review (SLR) method, employing the PRISMA flow diagram for article selection. Articles were selected based on inclusion and exclusion criteria, including relevance, educational context, and international journal indexing. This article provides crucial insights for educators and researchers to optimize student-centered learning. The analysis revealed that 67% agreed that the Multiple Intelligences approach significantly improved critical thinking skills, 20% reported no influence, and 13% noted effects only on certain skill types. This research also highlights challenges, including limited teacher knowledge and skills, a lack of supporting infrastructure, and difficulties integrating with traditional methods. Future studies are recommended to develop teacher training, enhance infrastructure, integrate Multiple Intelligences-based and traditional approaches, and conduct longitudinal studies to evaluate effectiveness.